Research and application of functional elements and newly defined function symbols for mechanical handling systems - Dang, Tan Nguyen (ASEAN engineering journal)
The assembly and handling technology guideline VDI 2860 mentions concepts, definitions and symbols in a handling technology. However, in this document there are limitations which make it more difficult to describe and outline a handling flowchart. The method of this study is based on assembling and manufacturing equipment, parameters and functions effecting the handling process, as well as methods used in assembling techniques to establish new concepts. The introduced function symbols are checked by application examples in a virtual assembly line. As the result of this study, necessary parameters are added to the existing elementary and compound functions. Moreover, new function symbols are formed and gathered in new function symbols of handling. The theoretical concept and the final application of these elementary and compound functions can be used for computer-aided planning (CAP) of handling systems.